Levelling out health inequalities in Poland during a systemic transition - Maniecka-Bryła, Irena; Bryła, Marek (Polish Journal of Public Health, 2009)
Aim. The paper aims at evaluating trends in mortality and life expectancy at birth (e0) which occurred in the consequence of the socio-economic transition in Poland.Material and methods. The data on deaths come from complete original databases which were created for 1991 and 2002. The data used to calculate the demographic characteristics of the population under study were taken from tables provided by the Central Statistical Office in Warsaw and the Regional Statistical Office in Lodz. In order to assess the impact of mortality changes in each age cohort on e0 developments, we applied the method proposed by J.H. Pollard. Moreover, in the statistical analysis, we used indices of intensity, structure and dynamics, direct standardisation and a u-test. Our point of departure was 1991, when the most unfavourable epidemiological situation was observed, in particular as far as the most important health problem, i.e. CVD, is concerned.Results. In the period under study, the overall mortality rate decreased from 14.6 per 1000 population to 13.0, but continued to be significantly higher than the national average (p < 0,001). The specific mortality rate due to CVD decreased from 775.8 per 100,000 to 518.1. The total mortality risk declined in the Lodz population in 2002 compared to 1991 and amounted to 0.892. E0 increased from 73.80 to 76.19 years among females, i.e. by 2.39 years, out of which as much as 0.71 years may be attributed to mortality reduction in the age cohort of 65-74. Among males, e0 grew by 4.1 years, from 63.96 to 68.06 years, and 1.03 years was a result of mortality reduction among those aged 55-64.Conclusion. The ongoing process of the socio-economic transition in Poland contributed to reducing disparities in the health situation. The reduction of mortality is reflected in e0 growth, to a higher extent among males than females.